Dynamical effects of the impact of falling mass on stiffened rectangular plate - Yaseen Abbood, Mazin (Anbar Journal of Engineering Sciences, 2012)
In this paper, the effect of using the strengtheners on the stress and deflection under the effect of a certain weight falling on plates made of aluminum alloys (Al Mg3)has been studied. The study was carried on through two aspects; experimentally and theoretically; theoretically by using (F.E.M LS. DYNA) program. After comparing the theoretical aspect and experimental aspect, greatly- close results at point of contact were found out, as follows: When using one strengthener, the stresses reduce by (14 %) and the deflection by (70%) with comparison of without stiffener case .When using two strengtheners at the ends, stresses reduce (77%) and the deflection (65%) .When using two strengtheners 8 cm apart, stresses reduce (56 % ) and the deflection ( 18%) . When using two strengtheners 4 cm apart, stresses reduce (60 %) and the deflection (31%)